Design for a hydraulic arbor press - Holzer, Hiram Adsit (My University, 1899)
Introduction: The following is a design for a tool to be of convenience for general machine shop use; such as pressing in bushings, shafts, mandrills, or tight fitting pins of any kind. It has a maximum power of seven tons and a sixteen inch throw. The cylinders are strong enough for pumping up to one thousand pounds pressure per square inch. It is to be operated by the hand, the effort being exerted thru a medium of oil instead of water. Computations. If 7 ton is the desired working pressure, then 7 X 2000 lbs. = 14000 lbs. the desired maximum pressure in pounds in the cylinder. The desired effort (45 lbs.) is to be exerted on a plunger thru a lever, in which the resistance bears a ratio to the effort of 1:3. If 45 lbs. is the maximum effort to be exerted on the lever, then 3 x 45 lbs. = maximum effort to be exerted on the lever, then 3 x 45 lbs. = 135 lbs., the resulting force exerted on the pump plunger. The desired area of pump plunger is ¼ square inch. Hence, a force of 135 pounds acting on a plunger ¼ square inch in area, will give a maximum working pressure of 540 pounds per square inch in the cylinder.
Citation: Holzer, Hiram Adsit. Design for a hydraulic arbor press. Senior thesis, Kansas State Agricultural College, 1898.
Morse Department of Special Collections
Keywords: Computations for Quter Cylinder; Inner Cylinder; Supportring Rods; Cap, Base; Pump Liner; Pump Attachments; Theses; Manuscripts (documents)